2013
DOI: 10.1371/journal.pone.0077514
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Woodland Caribou Movements in Response to Clearcuts and Roads across Temporal Scales

Abstract: Although prey species typically respond to the most limiting factors at coarse spatiotemporal scales while addressing biological requirements at finer scales, such behaviour may become challenging for species inhabiting human altered landscapes. We investigated how woodland caribou, a threatened species inhabiting North-American boreal forests, modified their fine-scale movements when confronted with forest management features (i.e. clearcuts and roads). We used GPS telemetry data collected between 2004 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Such research studies further demonstrated that not only can the barrier-effects of roads be species-specific across multiple taxa [47,49,55], they can influence some individuals within a species more than others [48,54]. Such differences were related to gender [48,50], age and/or body size (with smaller individuals being more restricted; [54]), and life history stage (such as the breeding season; [48,50]).…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 92%
See 2 more Smart Citations
“…Such research studies further demonstrated that not only can the barrier-effects of roads be species-specific across multiple taxa [47,49,55], they can influence some individuals within a species more than others [48,54]. Such differences were related to gender [48,50], age and/or body size (with smaller individuals being more restricted; [54]), and life history stage (such as the breeding season; [48,50]).…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 92%
“…One study highlighted that the barrier effects of roads are a particular concern for species that migrate, such as the pronghorn (Antilocapra Americana) [46]. Of the studies included in this review, nine identified the characteristics of road that influenced permeability, such as traffic volume [46][47][48], road width or the number of lanes [47,49], and road surface type. For the latter, five studies determined that paved roads impeded the movement of wildlife more than unpaved roads (including a number of species of reptiles and chimpanzees, Pan troglodytes) [47,[50][51][52][53].…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 99%
See 1 more Smart Citation
“…For example, roe deer (Capreolus capreolus) in southern Norway do not shift habitat use in response to predation risk during winter because they are constrained by other factors such as thermoregulation and starvation due to food limitation (Ratikainen et al 2007, Lone et al 2014. Determining optimal strategies in light of different trade-offs can be particularly challenging for highly mobile species that move across dynamic landscapes (Herfindal et al 2009, Beauchesne et al 2013. However, there is a general paucity of studies that have tested the landscape of fear model across dynamic environments involving highly migratory species at large spatial scales (tens to hundreds of thousands of square kilometers), probably due to logistical and technological challenges of working in such systems, particularly in open aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it is possible that selection is maladaptive and that areas with high 26-40 year old cutblock densities represent ecological sinks, where evolutionary cues and actual habitat quality diverge, resulting in poor habitat choices by caribou (Schlaepfer et al 2002). Maladaptive choices by caribou have been documented in numerous studies and are proposed as being a result of habituation, range fidelity, maternally learned selection strategies, or an inability of caribou to adjust to a rapidly changing environment (Faille et al 2010, Dussault et al 2012, Beauchesne et al 2013, Losier et al 2015.…”
Section: Discussionmentioning
confidence: 99%